Consequências da utilização da macho esterilidade genético citoplasmática no desempenho de híbridos de milho - Rodrigues, Luiz Augusto (2017)
The hybrid corn is one of the largest discoveries of the 20 th century. Its contribution for the increase of gain productivity is of deserved prominence. The adoption of simple hybrids by Brazilian agriculturists is growing and, since its discovery to the present day, the seed producing companies still face difficult ies in its production. Many hybrids of elevated productive potential are discarded in the initial phases of breeding due to low grain yield of the lineages. The difficulty in seed production derives especially from the need of detasseling the female genito r to occur hybridization. This activity is a laborious practice that employs a large number of people during the seasonal periods and heightens production cost, given the dependence on manual and scarce labor because of the need for manual transfer needed for the mechanic detasseing. The use of cytoplasmic genetic male sterility ease hybridization and collaborates for the production of hybrid seeds, decreasing production costs derived from detasseling and minimizing loss with excessive defoliation. For the conscientious use of cytoplasmic genetic male sterility, it is necessary to prove its efficacy in the agronomic performance of the hybrid. The present study was developed with the objective of comparing grain productivity of corn hybrids produced from the combination of two testers with five distinct lines of cytoplasm C “Charruá” versus its fertile cytoplasm isogenic. In eleven location, 20 simple hybrids of the first harvest of summer 2015/2016 and thirteen locations of the interim harvest of 2016 were evaluated. The experimental design used was of randomized blocks with two replicates. The characteristic evaluated was grain productivity, measured in tons of grains per hectare, correcting grain moisture at 13%. The agronomic characteristics of plant and corn ear height, resistance to disease, breaking and lodging were also measured. Individual and joint analyses of variance were conducted, and the Scott -Knott test was applied at 5% of probability for identifying differences between the different hybrids and their developments. Cytoplasm C was promising for the production of hybrids for not affecting agronomic performance, regardless of environment, location, parent or tester used. Therefore, it must be considered an excellent source of sterility for the use in the production of hybrid seeds in seed companies that wish to decrease the practice of detasseling